Evaluating stillborn and litter size as indicators of PRRSV detection in live piglets and the use of stillborn tongue fluids as risk-based samples for PRRSV monitoring - Machado, Isadora F.; Li, Peng; Xiao, Jinnan; Petznick, Thomas; Silva, Ana Paula P.; Osemeke, Onyekachukwu H.; Pantoja, Lucina Galina; Gauger, Phillip; Trevisan, Giovani; Silva, Gustavo S.; Linhares, Daniel C. L. (Frontiers in Veterinary Science, 2025)
IntroductionA risk-based approach to animal selection for sampling enhances pathogen detection by increasing the probability of selecting an animal harboring the pathogen while requiring a smaller sample size. Postmortem tongue fluids (TF) have emerged as a promising risk-based approach, with a PRRSV RNA positivity rate similar to serum, processing fluids, and family oral fluids. Thus, this study assessed the effect of stillborn presence, litter size, and PRRSV RNA detection by RT-qPCR in stillborn TF on the probability of having viremic piglets within the litter.MethodsSamples from 130 litters were collected within 12 hours after farrowing from two breeding herds. TF and intracardiac blood were collected from stillborns, and tail blood swabs were collected from liveborn littermates within the selected litters. Samples were individually tested for PRRSV RNA detection by RT-qPCR. Litters with ≤ 11 liveborn piglets were defined as small. Generalized linear regression models were used to evaluate the litter size, presence of stillborns, and stillborn PRRSV results on the probability that a litter or at least one liveborn littermate would test PRRSV-positive.ResultsThe live piglets’ mean positivity within the litter was 5.0%, while the total born was 4.6%. Litters with at least one stillborn had 12.5 times higher odds of having a PRRSV-positive result, and 4.8 times higher odds of having at least one viremic liveborn piglet. In small litters, the odds of having a PRRSV-positive result increased 12.2 times, whereas the odds of having a viremic liveborn littermate increased 10.8 times. When the stillborn TF was positive, the odds of having a viremic liveborn littermate increased 17.6 times.DiscussionIn conclusion, stillborn TFs were a reliable indicator of PRRSV status among litters. Liveborn piglets from litters with PRRSV-positive stillborn TF or small litters had greater odds of testing PRRSV-positive. Therefore, stillborn TF collection and targeting small litters improve PRRSV detection and support farrowing room biocontainment strategies.